2017
DOI: 10.1016/j.redox.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the effects of onion consumption on lipid mediators using a diet-induced model of hypercholesterolemia

Abstract: The levels and roles of lipid mediators can be modified in response to nutritional stimuli. The aim of this study was to investigate shifts in oxylipin and sphingolipid profiles stimulated by a hypercholesterolemic (HC) diet along with the modulating effects of onion introduced as an antioxidant functional ingredient characterized in the diet (HCO). Oxylipin and sphingolipid profiles were determined in plasma and tissues from Wistar rats using LC-MS/MS. Plasma ω-3 and ω-6 PUFA-derived oxylipins decreased in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The current results showed, however, that R+ treatment significantly reduced (p<0.05) TG levels when combined to the HC diet (C+/R+ rats) but failed to reduce TC levels. Contradicting findings with regard to TC responses have also been reported by others [14,15]. These discrepancies may have been a result of time length for resveratrol administration, likely being capable of TC reduction only when applied for longer periods (surely >5 days) [16].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The current results showed, however, that R+ treatment significantly reduced (p<0.05) TG levels when combined to the HC diet (C+/R+ rats) but failed to reduce TC levels. Contradicting findings with regard to TC responses have also been reported by others [14,15]. These discrepancies may have been a result of time length for resveratrol administration, likely being capable of TC reduction only when applied for longer periods (surely >5 days) [16].…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with other studies [14] done on rats fed comparable HC provoking diet for a period of 4 weeks, the HC-inducing diet used in our present trial also triggered remarkable (p<0.01) HC. The chronic combination of dietary cholate (cholic acid) with high cholesterol has been directly linked to HC, chiefly through the activation of adhesive and pro-inflammatory molecules and enzymes (namely, thromboxane A 2 and cyclooxygenases 1 and 2 [15]).…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic screening indicated specific metabolites and related metabolic pathways, which have encouraged the development of multiplatform metabolic fingerprinting of liver tissues. In addition, the present study has been motivated by a recent work that showed that onion supplementation ameliorated certain HC diet-related changes in liver oxylipins, which might be linked with a positive impact on the hepatic inflammatory process [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, it is known that the expression of hepatic fatty acid elongase and desaturase is regulated by nutrients, hormones and nuclear receptor agonists [ 25 ]. Additionally, onion and quercetin and quercetin derivatives, which are the main flavonols in onion, are able to affect the fatty acid metabolism by modifying the activity of numerous enzymes such as lipoxygenase (LOX), cyclooxygenase (COX) and cytochrome P450 (CYP) [ 19 , 26 , 27 , 28 ]. They are also able to alter the expression profiles of several lipid metabolism-related genes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other cellular proteins, like nuclear factor erythroid 2-related factor 2 (Nrf-2) [12,13,14], p53 [15,16], AMP-activated protein kinase [17,18], proliferator-activated receptor γ [19], and NAD-dependent deacetylase sirtuin-1 (SIRT1) [20] are also targets of allium-derived sulfur species. Consequently, many sulfur molecules have been reported to have anticancer properties [21,22,23,24], are anti-inflammatory [7,25,26,27], act as cytoprotective agents [28,29], function as inhibitors of metastasis [30,31], and alter lipid metabolism [32,33]. Additionally, molecules like diallyl trisulfide (DATS) release hydrogen sulfide gas (H 2 S) in the presence of glutathione and cysteine [34].…”
Section: Introductionmentioning
confidence: 99%